Exploring the Effects of Energy Consumption, Financial Market Development, and Urbanization on CO2 Emissions in GCC Countries: Cross-Sectional Dependence Analysis - Adow, Anass Hamadelneel; Mahmood, Haider; Furqan, Maham (International Journal of Energy Economics and Policy, 2025)
Financial Market Development (FMD), energy consumption, and urbanization can have significant effects on carbon emissions in fossil fuels-dependent GCC economies, which can be a hurdle in the way of targets 8 and 13 of the Sustainable Development Goals (SDGs). Thus, the influence of these factors on CO2 emissions has been tested in six GCC economies in the Environmental Kuznets Curve (EKC) framework. For this purpose, the Cross- Sectional Dependence econometrics has been utilized for the period 1990-2022. The results corroborate the EKC with threshold points of 13867 and 28158 in the long and short run, respectively. In both periods, energy consumption raises emissions. FMD reduces emissions and urbanization raises emissions in the long run. However, their short-run impacts are found insignificant. The study recommends encouraging FMD in the GCC region. However, urbanization and energy consumption should be controlled through policy interventions.